Reconstruction of the posterior cruciate ligament of the knee joint according to the technology «Onlay» - Golovakha, Maksim; Didenko, Inna; Krasnoperov, Sergiy; Titarchuk, Rostyslav; Benedetto, Кarl; Orljanski, Weniamin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Posterior crossed ligament injury is one of the most serious damages to the capsular-ligament complex of the knee joint, which is difficult to detect. Objective: to improve the treatment of patients with damage to the posterior crossed ligament of the knee by means of arthroscopic reconstruction using «Onlay» technology. Methods: 56 patients (44 men, 12 women) with posterior crossed ligament injury were operated. In 32 (57.14 %) cases, isolated posterior crossed ligament raptures were detected, in 24 (42.86 %) — combined injuries. Patients are operated using RetroDrill® reverse drilling technology using arthroscopic iimplantation of quadriceps tendon. Results: out of 56 patients in the period up to 6 years after the operation, it was possible to completely examine 21 individuals. Indicators on the VAS scale did not exceed 5 points in any case. In the assessment of mobility in the knee joint, 85 % of patients were assigned to a normal group, 15 % to almost normal. The joint function is recognized as normal in 5 % operated, almost normal — 15 %, moderate — 10 %, bad — 10 %. On the Kellgren-Lawrence scale, patients were divided into groups: 66.7 % — stage I with the onset of arthrosis, 28.57 % — stage II with slightly pronounced arthrosis, 4.76 % — stage III with moderate arthrosis. Conclusions: arthroscopic «everything inside» with RetroDrill® can be recommended as an alternative to posterior crossed ligament reconstruction. Averaged time, subjective and objective results were optimistic. At the heart of this are subjective pleasure, objective stability, a return to sports, avoiding arthrosis changes. Due to insignificant number of observations in the absence of a control group, the interpretation of results is limited.